Sustainability takes centre stage in public procurement - Caranta, Roberto (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2023)
This article delineates how a shift in the priorities of EU laws can change public procurement’s current centre of gravity from its fixation on the lowest price to that of a more balanced consideration of different societal goals. There is an acknowledgement that public money can meaningfully contribute to support for social justice and the fight against climate change and environmental degradation. To this end, the present EU legal framework, together with more advanced experiences in Italy and in a few other EU Member States, are illustrated before an analysis of the many initiatives currently under consideration by the EU law makers as per the European Green Deal and the Sustainable Products Initiative. The article then highlights the need to reconsider the theory of public procurement law and practice as well as the current EU legislative framework for public procurement (and concessions).